Simplified calculation method and stability analysis of top beam cooperative pile–anchor supporting slope structure - Ma, Tianzhong; Zhu, Yanpeng; Ye, Shuaihua (Frontiers in Materials, 2022)
Aiming at the problem of insufficient research on the action mechanism and stability calculation method of the top beam in the pile-anchor support structure, firstly the force and deformation model are established based on the elastic fulcrum method and the deformation coordination principle of the pile-anchor structure at the pile top and the anchor end in this paper. Secondly, the calculation model of the support structure under the synergy of the crown and beam and the simplified calculation method of the internal force, displacement and overall stability of the slope are constructed. Finally, combined with an engineering example, a MATLAB program was compiled for calculation, and the pile-anchor structures with crowned beams and without crowned beams were simulated and calculated by the finite element software PLAXIS 3D and Geo Studio. These three aspects are compared and verified. The results show that the internal force, deformation and minimum safety factor calculated by the method in this paper are basically consistent with the numerical simulation calculation results of the top beam condition; the existence of the top beam effectively enhances the bearing capacity of the pile body, and also restricts the displacement of the pile top development; the synergy of the crown and beam makes the safety factor of the slope increase significantly and improves the safety and stability of the slope. The research in this paper can provide a certain reference value for the theoretical calculation and design of the pile-anchor supported slope considering the top beam in engineering practice.